On the issue of the legal status and formation of election commissions in the Republic of Kazakhstan - Yerzhanova, F.A.; Bozhkarauly, А.; Lavnichak, А. (KSU Publ., 2018)
The subject of research of a scientific article is the election commissions in the Republic of Kazakhstan. The authors show the role and significance of this institution. In the present work, the issues of the constitutional and legal status of bodies carrying out the preparation and conduct of elections in the Republic of Kazakhstan are being investigated. The object of study are normative and legal acts regulating the formation and powers of election commissions in Kazakhstan. Based on a comparative legal analysis, the article deals with issues related to the organization and activities of election commissions in the Russian Federation and the Republic of Kazakhstan. Much attention is paid in the article to actual issues of functioning of election commissions, as well as to certain aspects of regulating the constitutional and legal status of these bodies. The modern problems of the domestic institute of election commissions indicate the need for further improvement of the constitutional and legal regulation of this institution in the context of the overall task of forming a civil society and a rule-of-law state in the Republic of Kazakhstan. The authors come to the conclusion that it is necessary to modernize election commissions in the direction of establishing a system of permanent election commissions. The article also proposes improvement of the procedure for forming the composition of election commissions in order to ensure equal representation of political parties participating in elections.
Қазақстан Республикасындағы сайлау комиссияларының құқықтық мəртебесі мен қалыптастыру мəселесі туралы
К вопросу о правовом статусе и формировании избирательных комиссий в Республике Казахстан
Keywords: The Constitution of the Republic of Kazakhstan; direct democracy; elections; electoral law; election commissions of the Republic of Kazakhstan; the formation of election commissions; the legal status of election commissions; the rule of law; civil society